PATTERN OF THYROID DISORDERS AMONG PATIENTS IN HAZARA DIVISION, PAKISTAN - Nasir Hussain Shah Kazmi; Saima Gillani; Abdul Rauf; Haider Zaman; Shahzad Najeeb; Iftikhar Ahmad (Gomal Journal of Medical Sciences, 2018)
Background: Thyroid disorders are a commonly encountered problem in hilly areas of Pakistan. The objectives of the study were to determine the frequency and distribution of thyroid disorders among patients presenting with suggestive signs & symptoms of thyroid disorders in Hazara Division, Pakistan. Material and Methods: This cross-sectional study was conducted in Departments of Medicine and Pediatrics & Neonatology, Ayub Medical College, Abbottabad, KP, Pakistan from January, 2017 to January, 2018. Exclusion criteria was patients taking medicines such as Lithium and Cordarone. Sample size was 55 selected using consecutive sampling technique. Reference values were taken as follows; serum TSH=0.4-4.0 µIU/L, serum T3=100-200 ng/dL), serum T4=5-13.5 µgm/dL. Demographic variables were sex and age. Research variables were thyroid status (euthyroid/ hyperthyroid/ hypothyroid) and levels of thyroid function tests (TFT). Categorical variables such as sex and thyroid status were calculated by frequency and percentages whereas numeric variables such as age and TFT by Mean and SD. Descriptive statistics were calculated using SPSS Version 20. Results: Out of the total 55 patients, 11 patients were males and 44 patients were females. The minimum age was 20 years, maximum age was 90 years. Mean age was 43.24 years±15.118. Out of the total 55 patients, 14 (25.5%) were euthyroid, 30 patients (54.5%) were hyperthyroid and 11 (20%) patients were hypothyroid. Out of the 14 patients that were euthyroid, seven were males and seven were females. Out of the 30 hyperthyroid patients 26 were females and only 4 were males. All 11 hypothyroid were females. Conclusions: Hyperthyroidism is more common thyroid disorder in Hazara Division specially in adult females.